Additive genetic variance for lifetime fitness and the capacity for adaptation in an annual plant. (26th August 2019) - Kulbaba, Mason W.; Sheth, Seema N.; Pain, Rachel E.; Eckhart, Vincent M.; Shaw, Ruth G.
Abstract: The immediate capacity for adaptation under current environmental conditions is directly proportional to the additive genetic variance for fitness, VA (W). Mean absolute fitness, W ¯, is predicted to change at the rate V A ( W ) W ¯, according to Fisher's Fundamental Theorem of Natural Selection. Despite ample research evaluating degree of local adaptation, direct assessment of VA (W) and the capacity for ongoing adaptation is exceedingly rare. We estimated VA (W) and W ¯ in three pedigreed populations of annual Chamaecrista fasciculata, over three years in the wild. Contrasting with common expectations, we found significant VA (W) in all populations and years, predicting increased mean fitness in subsequent generations (0.83 to 6.12 seeds per individual). Further, we detected two cases predicting "evolutionary rescue, " where selection on standing VA (W) was expected to increase fitness of declining populations ( W ¯ < 1.0) to levels consistent with population sustainability and growth. Within populations, inter‐annual differences in genetic expression of fitness were striking. Significant genotype‐by‐year interactions reflected modest correlations between breeding values across years, indicating temporally variable selection at the genotypic level that could contribute to maintaining VA (W). By directly estimating VA (W) and total lifetime W ¯, our study presents an experimental approach for studies of adaptive capacity in the wild.